Pengaruh Relaksasi Progresif Dan Aromaterapi Lavender Terhadap Penurunan Kecemasan Pada Pasien Pre Operasi Dengan Spinal Anestesi - Fatmawati, Dian Prastika; , Arina Maliya, S.Kep., M.Si., Med (2016)
Preoperative Nursing is the early stages of the erioperative nursing. Preoperative begins when the decision was taken to perform surgical intervention. Anxiety is a normal adaptive response to stress because it will do the surgery. The prevalence of anxiety disorders range from 6-7% of the general population. Research using HARS, showed the prevalence of anxiety disorders by 8-12%.Factors that can reduce anxiety among others with progressive relaxation technique and administration lavender aromatherapy. This study aims to investigate the influence of progressive relaxation and aromatherapy lavender to decrease reoperative anxiety in patients with spinal anesthesia. This research is quantitative with quasi experimental and nonequivalent control group design with pre-post test design. The study was conducted at the installation of the Central Surgical Hospital Dr Moewardi Surakarta. The study sample consisted of 15 patients to the control group and 15 patients to the experimental group were given progressive relaxation and aromatherapy lavender been using accidental sampling technique. The collection of data obtained from questionnaires Hars (Hamilton Anxiety Rating Scale). Data analysis was performed using analysis of paired sample t-test and independent sample t-test. The results showed that the test results paired sample t-test there is no difference in the average anxiety pre-test and post-test in the control group (p-value = 0.698), and there are differences in the average anxiety pre-test and post test experimental group ( p-value = 0.001). The test results of independent sample t-test result that there is no difference in the average pre-test anxiety between the experimental group and control group (p-value = 0.959) and there are differences in the average anxiety post test between the experimental group and control group (p value = 0.019). Results from this study is there influence of progressive relaxation and aromatherapy lavender to decrease preoperative anxiety in patients with spinal anesthesia.